Prosperity, Prophecy and the COVID-19 Pandemic: The Healing Economy of African Pentecostalism - Ukah, Asonzeh (Pneuma, 2020)
One of the intractable problems of Africa is socioeconomic development. It is a “wicked problem” that has defied decades of tinkering and tweaking of economic policies and government interventions. Like many African governments that succeeded oppressive colonial governments, many religious organizations frequently promise their members the help of divine power to deliver development. African Pentecostalism, especially the prosperity variant, has been at the forefront of promising to make its members healthy and wealthy through divine means. How the theology of plenty and healing has practically improved the economic and therapeutic systems of Africa is a question of debate. Some scholars, in line with pentecostal self-representation, claim that Pentecostalism inspires development from below. This essay critiques this self-image of African Pentecostalism in the context of African economic indices and the raging and ravaging coronavirus disease pandemic. The COVID-19 pandemic presents an important challenge but also an opportunity to test the doctrines and claims of pentecostal leaders. In the attempt to cater to leaders’ economic self-interest, pentecostal responses to the pandemic have, however, been uncoordinated and have failed adequately to mobilize resources that serve its members and the larger society in their moment of needs.
free
Keywords: African Pentecostalism; COVID-19; faith healing; pandemic; poverty; prosperity